Functional Income Distribution and Secular Stagnation in Europe: An Analysis of the Post-Keynesian Growth Drivers - Alcobia, J.; Barradas, R. (REM Working Paper Nº 2023/283, 2023)
The majority of policymakers in the more developed countries have engaged in Reaganomics and Thatcherism in the last four decades by privileging the adoption of wage restraint policies to sustain economic growth. During that time, the wage share has registered a sustained fall, and economic growth has been rather dismal, which seems to support the theoretical claims of post-Keynesian economics that wage restraint policies are detrimental to economic growth because their disruptive effects on private consumption do not counterbalance their supportive effects on private investment and net exports. We analyse the relationship between the wage share and economic growth by performing a panel data econometric analysis of all European Union countries from 1981 to 2021. Results confirm that wage share positively influences economic growth in the European Union countries, which in reality is a wage-led growth model. Results also show that the decline of the wage share has represented one of the main constrainers of growth in all European Union countries in the last four decades, particularly in the euro area countries. These results suggest that policymakers in the European Union countries should adopt pro-labour policies in order to revert the decreasing (increasing) trend of the wage (profit) share and avoid the consolidation of a secular stagnation in Europe.